PZT ceramics obtained from mechanochemically synthesized powders - Brankovic, Z.; Brankovic, G.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2003)
PZT ceramics were obtained from the mechanochemically synthesized powders. Milling and sintering conditions were optimized based on results of density measurements, as well as on microstructural and electrical characterization. As a result, highly dense and homogeneous ceramics were obtained. Excellent microstructural properties resulted in good electrical properties. Samples showed values of dielectric constants reaching 12800 at the Curie temperature, as well as low dielectric loss under the optimal processing conditions. High values of remanent polarization, reaching 60 muC cm(-2), indicate high internal polarizability. (C) 2003 Kluwer Academic Publishers.